The Routine Use of Prophylactic Oxytocin in the Third Stage of Labor to Reduce Maternal Blood Loss - Akiko Kuzume; So Sugimi; Sachie Suga; Hiroshi Yamashita; Ichiro Yasuhi (Hindawi Limited, 2017)
Objective. To demonstrate whether or not the routine use of prophylactic oxytocin (RUPO) reduces the blood loss and incidence of postpartum hemorrhaging (PPH). Methods. We used a prospective cohort and a historical control in a tertiary perinatal care center in Japan. In the prospective cohort, we introduced RUPO in April 2012 by infusing 10 units of oxytocin per 500 mL of normal saline into a venous line after anterior shoulder delivery (RUPO group). In the historical control, oxytocin was administered via a case-selective approach (historical control group). We included completed singleton vaginal deliveries and compared the volume of blood loss and the incidence of PPH between the groups. Results. We found a significantly lower volume of blood loss (520±327 versus 641±375 mL, p<0.001) and a lower incidence of PPH (6.1% versus 14.0%, p<0.001) in the RUPO group (n=392) than in the control group (n=407). Although the oxytocin dose was significantly higher in the RUPO group (12.8±6.7 versus 10.1±8.0 IU, p<0.001), no adverse outcomes were observed to be associated with RUPO. Conclusions. The introduction of RUPO significantly reduced blood loss and the incidence of PPH during completed singleton vaginal deliveries without an increase in adverse effects.